Pengendalian Persediaan Bahan Baku untuk Mengatasi Out of Stock di Perusahaan Karoseri - Ronny Hariono; I Nyoman Sutapa (Jurnal Titra, 2023)
Karoseri is a car body company that produces vehicle bodies and frames. The problem faced by the company is that the inventory of raw materials in the warehouse is often out of stock. These problems can cause delays in production schedules and overtime for workers. The existence of this problem is caused by 2 parties, between suppliers and karoseri. From the supplier's side, the lead time for goods to arrive at the warehouse is uncertain. From karoseri’s side, the amount of safety stock has not been updated and there is no order planning method or system used. The need for raw materials at karoseri is also variable or probabilistic, so the proposed solution is to use the continuous review and periodic review methods. The results of the calculation and simulation of the raw material requirements per day, it is found that the continuous review method gets the cheapest total inventory cost. After finding the best method for ordering raw materials, a Standard Operating Procedure (SOP) is made regarding the planning of ordering raw materials so that the parties involved can understand and understand how to use the continuous review method calculation for ordering raw materials.